A Retrospective Study on the Use of Chinese Patent Medicine in 24 Medical Institutions for COVID-19 in China - Nan Zhang; Nannan Shi; Siyu Li; Guoxiu Liu; Yonglong Han; Li Liu; Xin Zhang; Xiangwen Kong; Bihua Zhang; Wenpeng Yuan; Yi Liu; Deqiang Deng; et al. (Frontiers Media S.A., 2020)
Objective: This research aims to analyze the application regularity of Chinese patent medicine during the COVID-19 epidemic by collecting the names of the top three Chinese patent medicines used by 24 hospitals in 14 provinces of China in four time periods (January 20-22, February 16-18, March 01-03, April 01-03, 2020), and explore its contribution to combating the disease.Methods: 1) We built a database of the top three Chinese patent medicines used by 24 hospitals. 2) The frequency and efficacy distribution of Chinese patent medicine were analyzed with risk areas, regions, and hospitals of different properties as three factors. 3) Finally, we analyzed the differences in the use of heat-clearing and non-heat-clearing medicines among the three factors (χ2 test) and the correlation between the Chinese patent medicine and COVID-19 epidemic (correlation analysis) with SPSS 23.0 statistical software.Results: 1) The heat-clearing medicine was the main use category nationwide during January 20-22, 2020. Meanwhile, there was a significant difference in the utilization rate of heat-clearing and non-heat-clearing medicine in different risk areas (p < 0.01). 2) The variety of Chinese patent medicine was increased nationwide during February 16-18, 2020, mainly including tonics, blood-activating and resolving-stasis, and heat-clearing medicines. Meanwhile, there was a significant difference in the utilization rate of heat-clearing and non-heat-clearing medicine in the southern and northern regions (p < 0.05). 3) Tonics, and blood-activating and resolving-stasis medicines became the primary use categories nationwide during March 01-03, 2020. 4) The tonics class, and blood-activating and resolving-stasis medicine were still the primary categories nationwide during April 01-03, 2020. Meanwhile, there was a significant difference in the utilization rate of heat-clearing and non-heat-clearing medicine in different risk areas (p < 0.01).Conclusion: Chinese patent medicine has a certain degree of participation in fighting against the COVID-19. The efficacy distribution is related to the risk area, region, and hospital of different properties, among which the risk area is the main influencing factor. It is hoped that future research can further collect the application amount of Chinese patent medicine used in hospitals all over the country, so as to perfectly reflect the relationship between Chinese patent medicine and the epidemic situation.